Corporate social responsibility - Viernes, Annaliza B. (Manila : Unlimited Books Library Services & Publishing Inc., 2022)
"This book was motivated by the desire to bridge the best practices of job analysis and design of various industries to the academe setting in today's 21st century. We believe that students must appreciate elements of corporate social responsibility to reduce the gap of learning from theories and learning in applications."
Includes references.
English.
Keywords: Corporate governance; Social responsibility of business